PENGARUH KEMAMPUAN DAN FASILITAS KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN PRODUKSI PADA PT. MARITA MAKMUR JAYA KECAMATAN RUPAT, KABUPATEN BENGKALIS - Silfa Rino; Nuryanti '; Restu ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research at PT. Marita Makmur Jaya which reside in Kecamatan Rupat Kabupaten Bengkalis, started since March month 2014 till finish. Amount of sampel in this research is counted 90 people or totalize the overall of population. Intake of sampel relied on census method. While to analyse data, writer use doubled linear regression method constructively peripheral of SPSS Version 17.0. Pursuant to result of test of F known that ability variable and facility work by together have an effect on signifikan to employees work productivity part of production at PT. Marita Makmur Jaya, Kecamatan Rupat Kabupaten Bengkalis. Pursuant to result of test of known that ability variable variable and facility work by parsial have an effect on signifikan to employees work productivity part of production at PT. Marita Makmur Jaya, Kecamatan Rupat Kabupaten Bengkalis. Contribution influence of ability variable and facility to employees work productivity part of production at PT. Marita Makmur Jaya, Kecamatan Rupat Kabupaten Bengkalis equal to 50.1 %, while the rest 49.9 % influenced by other variable which do not research in this research.Keywords: Productivity, Ability, and Facility.